Principles and methods of law and economics: basic tools for normative reasoning - Georgakopoulos, Nicholas L. (Cambridge, 2005)
This is an introductory book that targets the reader who has the ambition to apply economic analysis but may be missing a technical introduction to its mathematical techniques or seeks a structured elaboration of its philosophical principles. The book juxtaposes economic analysis with moral philosophy, political theory, egalitarianism, and other methodological principles and then passes to the details of methods such as model-building, derivatives, differential equations, statistical tests, and the use of computer programs
Keywords: Law and economics